Fotossíntese e anatomia de raiz em genótipos de Coffea arabica L. sob déficit hídrico - Andrade, Lissa Izabel Ferreira de (2019)
Coffee trees during their cycle are subjected to periods of water deficit and the complexity of their responses are not yet fully understood. Understanding adaptive responses mechanisms are necessary to predict survival strategies and contribute to the improvement of coffee cultivation under water deficit conditions. The aim was to identify if physiological responses can induce anatomical changes in Coffea arabica L. genotypes under conditions of water deficit that promote drought tolerance. The experiment design was a randomized block design with four materials of C. arabica L. (cvs. Catiguá MG3 and Catuaí IAC; genotypes G7 and G19), grown in pots with 22L capacity and maintained in two contrasting water conditions, with and without water restriction, in a 4x2 factorial scheme, with five replications. Throughout the experimental period it was evaluated the pre-dawn xylem water potential (Ψpd), relative water content (RWC), gas exchange, CO2 and light response curves, photosynthetic pigments content, and root anatomy. The water deficit was responsible to reduce Ψpd and RWC of all four cv./genotypes, being G7 the genotype with lower values under these conditions. The disturbance of the water status of plants under water deficit conditions was responsible for decreasing photosynthesis (A), transpiration (E), and stomatal conductance (gs). A reduction in the maximum assimilation rate of the response curve as a function of the photosynthetically active radiation (AmaxQ) was observed in the photosynthesis response curves for all plants under water deficit. For the CO2 response curve was observed that under lower water availability, there was a reduction in the maximum carboxylation rate (Vcmax), indicating a decrease in the carboxylase activity of Rubisco. The genotype G19 under water deficit showed lower values of regeneration of Ribulose 1,5-biphosphate (RuBP), dependent on the electron transport rate (Jmáx) and the triose-phosphate utilization (TPU), while cv.Catuaí had lower mesophyll conductance (gm). The reduction of Vcmaxand Jmaxindicates that lower photosynthetic rates in plants under water restriction are related to the decrease in the carboxylase activity of Rubisco. In the roots of plants under water deficit, it was observed anatomical modifications in root cross-sectional area of genotypes G7 and G19, in vascular cylinder area of cv.Catuaí, and in the number of root hairs of genotype G7, which may be characterized as strategies in order to enhance the capacity of retention and absorption of water, respectively. The genotype G19 had an increase in the number of tracheal elements and metaxylem poles, as well as the cv.Catiguá and the genotype G7 showed a reduction in the diameter of tracheal element. The genotypes G7 and G19 had higher photosynthetic capacity than cvs.Catiguá and Catuaí in the condition of larger water availability; however when exposed to water deficit conditions there was a reduction of this characteristic for all cv./genotypes, affecting mainly biochemical process. The anatomical changes in coffee trees under water deficit showed that these strategies may contribute to increase the tolerance of each cv./genotype to these conditions.